Composition art for decoding of Bangtan Sonyeondan‘s artwork - Jittham, Jullajit; Chaturongakul, Kham (Asian Journal of Traditional and Innovative Arts and Textiles, 2024)
This research article has the following objectives: to analyze the composition and art in BTS’s music videos "Idol," "Boy with Luv," and "Dynamite," and to produce creative video media to provide knowledge about composition art. By analyzing the composition art used to create video media design works and analyzing satisfaction data from the sample group. The research results found that composition art appears in terms of color use, all three music videos use warm and cool colors, using a variety of color pairings and different tones to influence the color psychology of each music video. Regarding the illustrations, each song features unique illustrations that aim to convey the meaning of the song’s content. On the lettering side, artificial letters are commonly used. This is because the designers wanted to tailor the design to match the specific concept of the song, the use of capital letters is intended to capture the audience’s interest and in terms of composition, focus on balanced placement to make the image look balanced. Because throughout the song there are alternating images, colors and moving elements. Therefore, the image is usually centered so that it remains in the viewer’s eye. Effects and camera angles are used to help keep the audience from getting bored with the focus point. As for the production of creative video media, it provides knowledge about composition art. By producing 5 episodes of video media, it was found that the basic understanding of composition art before viewing the video media as a whole was at a moderate level of understanding. with an average of 2.64 and after viewing the overall picture was at the level of understanding with an average of 4.17. The average after watching video media increased from before watching video media at a statistical significance of 0.01 and the results of the analysis of satisfaction in watching video media The overall picture is at the highest level. with an average of 4.42.